A new e-Testing platform with grading strategy on essays - Gushev, Marjan; Kostoska, Magdalena; Ristov, Sasko (IEEE, 2017)
In this paper, we elaborate a new e-Testing platform based on essay questions and a special grading procedure. Our platform enables anonymity during the grading process, equal treatment of all answered questions, grading strategy for each question, easier and faster grading process. The realized user experience analysis shows that the students are satisfied with this new platform, especially that it enables them to more easily understand what they have missed during the provision of answers, and it enables continual learning even after the evaluation. Almost all students that have failed the course also were satisfied of the system. The system is described with its functions, benefits and impact.
Keywords: E-Testing; essay grading; MOOC; E-learning